Development of Low Impact Aerobics Gymnastics Model for the Elderly Level at Sanggar Mawar Jingga Palembang City - Rohayu, Septiani; Lanos, Muhsana El Cintami; Handayani, Widya (Yayasan Sembilan Pemuda Indonesia, 2023)
The problem in this study is that the members of gymnastics in the Mawar Jingga studio in Palembang City have reached the age of elderly, but they are still enthusiastic about participating in gymnastics. The problem is that they have difficulty during gymnastics because the movement and tempo of the music do not match their abilities. Therefore, researchers aim to develop a low impact aerobic exercise model for the elderly level at the Mawar Jingga studio in Palembang City. This research is research and development, this research is carried out through the stages of needs analysis, planning, making initial product designs, material and media expert validation. Furthermore, the product is tested on the elderly through small-scale trials, revisions, large-scale trials, revisions and final products. The product test subjects were elderly in the Sanggar Mawar Jingga studio in Palembang City. The data from the expert validation results got a value very valid category. It can be concluded that the low impact aerobic exercise model product developed is suitable for use by the elderly.